MOTIVASI KERJA APARAT PEMERINTAH DESA WASIAN KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Lensun, Junifer Frederik; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (Sam Ratulangi University, 2019)
The purpose of this research is to determine the motivation impact of village governmentapparatus in Wasian village of Dimembe district of North Minahasa Regency.This study uses a descriptive-qualitative approach method. Work motivation is seen from the sixdimensionalwork motivation of Hezberg. The research informant of the village head, village secretary, headof affairs, and the Dusun/guard heads. Data collection uses interview guidelines, while the analyticaltechniques used are interactive model analyses of Miles and Hubernann.Based on the results of the study concluded: 1. The motivation of the government apparatus of Walianvillage is generally still less maximum. Acceptable allowances have not been able to realize the high workingmotivation among village government officials. 2. The motivation of the village government apparatus toachieve high achievement is still lacking/low. The village apparatus works as it is without pursuingachievements. 3. Motivation to work the village government apparatus to gain recognition of the results ofwork is still lacking/lower. The village apparatus works as it is and does not think of recognition of theresults of work/achievement. 4. Motivation to work the village government apparatus to get a task whoseresponsibility is greater still less/lower. 5. Motivation for the work of village government apparatus to gainprogress on the results of the work is still low. The village government apparatus only works according toexisting assignments, and does not work to pursue progress. 6. The motivation to work the villagegovernment apparatus to gain the opportunity to develop knowledge and skills in the implementation oftasks is also low, because the opportunity for it is also very rareKeywords: Work motivation, village government apparatus